Graduate Competency Patterns for Strategic Differentiation in Bukhara HEIs - Feruz Yuldashev (Academia Open, 2025)
General Background: In today’s global knowledge economy, the competitiveness of higher education institutions (HEIs) increasingly depends on their ability to align graduate competencies with labor market expectations. Specific Background: This is particularly relevant in regional contexts like Bukhara, Uzbekistan, where institutions must adapt to evolving demands while preserving traditional education values. Knowledge Gap: Despite global emphasis on employability, limited empirical research has analyzed how specific competencies influence HEI competitiveness in transitional economies. Aims: This study investigates the impact of five key graduate competencies—communication, creativity, self-competence, IT competence, and social competence—on employer evaluations to inform strategic competitiveness management. Results: Using data from 363 employers and regression analysis, the findings reveal that communication and creativity are the most significant predictors, explaining 47.9% of the variance in employer ratings. Institution-specific models further highlight varied strengths across five HEIs. Novelty: The study provides a competency-based, data-driven framework for HEI competitiveness management that differentiates institutional profiles rather than applying uniform standards. Implications: These insights offer HEI leaders targeted guidance for curriculum development and strategic planning, demonstrating how employer feedback can serve as a powerful tool for institutional enhancement and labor market alignment.Highlight : Communication and creativity are the strongest predictors of graduate employability. Each university exhibits unique competency strengths, requiring tailored improvement strategies. Competency-based employer evaluations support evidence-driven competitiveness management. Keywords : Higher Education, Graduate Competencies, Institutional Competitiveness, Employer Evaluation, Regression Analysis